2004
DOI: 10.4049/jimmunol.173.3.1834
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a CD4+CD28− Granzyme B+, Cytomegalovirus-Specific T Cell Subset after Recovery of Primary Cytomegalovirus Infection

Abstract: Cytotoxic CD4+CD28− T cells form a rare subset in human peripheral blood. The presence of CD4+CD28− cells has been associated with chronic viral infections, but how these particular cells are generated is unknown. In this study, we show that in primary CMV infections, CD4+CD28− T cells emerge just after cessation of the viral load, indicating that infection with CMV triggers the formation of CD4+CD28− T cells. In line with this, we found these cells only in CMV-infected persons. CD4+CD28− cells had an Ag-prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
289
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(318 citation statements)
references
References 52 publications
(46 reference statements)
19
289
3
Order By: Relevance
“…3B) and granzyme B (data not shown), thus corresponding to a described subset of HCMV-specific CD4 + CTL [43]; it is noteworthy that both perforin and granzyme B were also detected in CD4 + NKG2D -cells ( Fig. 3B; data not shown).…”
Section: Distribution Of Ilt2 Kir and Cd94/nkg2 Nkr On Hcmv-stimulatmentioning
confidence: 72%
“…3B) and granzyme B (data not shown), thus corresponding to a described subset of HCMV-specific CD4 + CTL [43]; it is noteworthy that both perforin and granzyme B were also detected in CD4 + NKG2D -cells ( Fig. 3B; data not shown).…”
Section: Distribution Of Ilt2 Kir and Cd94/nkg2 Nkr On Hcmv-stimulatmentioning
confidence: 72%
“…The appearance of HCMV-specific IFN-γ-producing CD4 + T cells in asymptomatic recipients of CMV-positive allotransplants was specifically correlated with containment of viral control [38] and CD4 + T-cell lines specific for certain HCMV CD4 + T-cell antigens were shown to be cytolytic [23,35]. Interestingly, a very recent study reported the existence of high numbers of multifunctional pp65-specific CD4 + T cells in bronchoalveolar lavage-derived lung mononuclear cells of lung transplant recipients with chronic CMV infection, which correlated with mucosal viral control [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of pathogenic MCMV infection of hemoablated recipients, CD4 + T cells were considered not to display direct antiviral activity [33] and thus were generally not considered for T-cell immunotherapy protocols. However, studies of HCMV-specific CD4 + T cells in humans [34,35] and recent clinical studies [36] have indicated a possible protective role of CMV-specific CD4 + T-cell-mediated immunity. In this study, using a recently developed TCR transgenic mouse recognizing an MCMV-specific CD4 + T-cell epitope within the M25 protein, we characterized the development, phenotype, and antiviral functions of virus-specific CD4 + T cells during Our data provide direct evidence for a role of MCMV-specific CD4 + T cells in adoptive T-cell immunotherapy of CMV disease.…”
mentioning
confidence: 99%
“…These cells were found to be MHC class IIrestricted cytotoxic T-cells. 41,42 Cassaza 22 reported their ability to kill CMV Ag-loaded B-LCLs.…”
Section: Discussionmentioning
confidence: 99%